Entrepreneurial Valuation An Entrepreneur's Guide to Getting into the Minds of Customers - Packard, Mark (De Gruyter, 2022)
Value is a verb, and entrepreneurial valuation is the process of figuring out what others (should) value. The process is a challenging one, fraught with difficulties. If you are considering your own entrepreneurial journey, how do you start? How do you come up with a good idea? How do you know if your idea is good or if consumers would pay for it? Entrepreneurial Valuation brings to life cutting-edge research on value theory, challenging the prevailing wisdom that entrepreneurial valuation is as simple as asking consumers what they want. In fact, consumers often don't know what they (should) want. Value is a learning process, and consumers are learning what to want over time. Entrepreneurial Valuation will teach you how to follow consumers through this value learning process until you understand them enough to lead themon their journey.